2018
DOI: 10.1167/iovs.17-23437
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Retinal Microvasculature and Visual Acuity After Antivascular Endothelial Growth Factor Therapy in Retinal Vein Occlusion

Abstract: PURPOSE. To investigate the changes in the retinal microvasculature during the course of anti-VEGF therapy in eyes with macular edema due to retinal vein occlusion (RVO) and their association with visual outcomes.METHODS. The vessel density (VD) and foveal avascular zone (FAZ) area in the superficial capillary plexus (SCP) and deep capillary plexus (DCP) were quantitatively measured by optical coherence tomography angiography (OCTA) in 48 consecutive eyes with RVO before and 1, 3, 6, 9, and 12 months after ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
35
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 47 publications
4
35
1
Order By: Relevance
“…In this study, MMP-1 and MMP-2 were positively correlated with macular superficial capillary density. Winegarner et al reported a positive correlation between better BCVA and superficial capillary density in RVO patients (27); whereas we observed a negative correlation between MMP1 and visual improvement. In our study, the aqueous humor level of MMP1, superficial capillary density and visual improvement do not support each other.…”
Section: Discussion:contrasting
confidence: 82%
“…In this study, MMP-1 and MMP-2 were positively correlated with macular superficial capillary density. Winegarner et al reported a positive correlation between better BCVA and superficial capillary density in RVO patients (27); whereas we observed a negative correlation between MMP1 and visual improvement. In our study, the aqueous humor level of MMP1, superficial capillary density and visual improvement do not support each other.…”
Section: Discussion:contrasting
confidence: 82%
“…Progression of ischaemia is a significant cause of permanent vision loss in eyes with RVO 46. In this study, progression of capillary nonperfusion was observed in six (8.8%) eyes despite use of anti-VEGF over the 5 years of follow-up.…”
Section: Discussionmentioning
confidence: 52%
“…Recent studies [34,35] focused on vessel density changes and macular perfusion in RVO after anti-VEGF using OCTA technology. Andrew Winegarner et al [34] found no significant changes in mean VD 12 months after anti-VEGF injections in patients with RVO, although higher VD and a smaller FAZ were associated with better BCVA. Other authors [24,35,36] confirmed no significant variation of macular VD after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We mentioned above that it is possible to hypothesize that masking effect or retinal vessel displacement due to edema could justify the reappearance of the vessels that were poorly identified before treatment [32,33,34,35].…”
Section: Discussionmentioning
confidence: 99%